EKSTRAK AIR LIMBAH TAHU SEBAGAI SUBSTRAT ALTERNATIF PERTUMBUHAN Acetobacter xylinum UNTUK SINTESIS POLISAKARIDA EKSTRASELULER (Nata de Tofu) - , RETNO SETYASTI, Prof. Dr. A. Endang Sutariningsih Soetarto, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The tofu industry produce more wastes rather than tofu production. Tofu industrial wastes consisted of solid and liquid wastes, containing a lot of organic compounds such as carbohydrates (12-30%), proteins (35-35%), fats (18-32%) and inorganic compounds or minerals included nitrogenous compounds (1,15%), phosphates (0,18%), calcium (0,19%), iron (0,04%), water (0,09%) and very low pH. Based on pH and nutrient contents, those waste had a potential environmental pollutants. In order to remove pollutants, many efforts had been done by physically, chemically and biologically treatments. One alternative way to utilize those wastes was to be used Acetobacter xylinum. Under low pH Acetobacter xylinum could grow and form extracellular polysaccharide called nata. The aims of the research were to utilize solid waste from tofu home industry as media for Acetobacter xylinum producing nata